η→γγ Decay width via the Primakoff cross section - Rodrigues, T. E.; Arruda-Neto, J. D.T.; Mesa, J. [UNESP]; Garcia, C.; Shtejer, K.; Dale, D.; Nakagawa, I.; Cole, P. L. (American Physical Society (APS), 2008)
Incoherent η photoproduction in nuclei is evaluated at forward angles within 4 to 9GeV using a multiple scattering MonteCarlo cascade calculation with full η-nucleus final-state interactions. The Primakoff, nuclear coherent and nuclear incoherent components of the cross sections fit remarkably well previous measurements for Be and Cu from Cornell, suggesting a destructive interference between the Coulomb and nuclear coherent amplitudes for Cu. The inelastic background of the data is consistently attributed to the nuclear incoherent part, which is clearly not isotropic as previously considered in Cornell's analysis. The respective Primakoff cross sections from Be and Cu give Γη→γγ=0.476(62)keV, where the quoted error is only statistical. This result is consistent with the Particle Data Group average of 0.510(26)keV and in sharp contrast (∼50%) with the value of 0.324(46)keV obtained at Cornell. © 2008 The American Physical Society.